2013
DOI: 10.1371/journal.pone.0079235
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Optoinjection of Intact Tobacco BY-2 Cells Using a Reconfigurable Photoporation Platform

Abstract: A tightly-focused ultrashort pulsed laser beam incident upon a cell membrane has previously been shown to transiently increase cell membrane permeability while maintaining the viability of the cell, a technique known as photoporation. This permeability can be used to aid the passage of membrane-impermeable biologically-relevant substances such as dyes, proteins and nucleic acids into the cell. Ultrashort-pulsed lasers have proven to be indispensable for photoporating mammalian cells but they have rarely been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…[1][2][3][4][5] Cell membrane perforation by focused femtosecond laser pulses provides an exclusive technology to introduce external molecules into a single cell, i.e., optoinjection, without significant cell damage because of a nonlinear interaction in a tiny focused spot. [6][7][8][9] Recently, the use of nanoparticles or microparticles has been accelerating attractive achievements to expand the capability of ultrashort laser optoinjection technology toward simultaneous treatment of multiple cells. Chakravarty et al 10 reported the delivery of DNA, protein, and fluorescence molecules into cells in a cuvette by using carbon black nanoparticles and a femtosecond laser.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Cell membrane perforation by focused femtosecond laser pulses provides an exclusive technology to introduce external molecules into a single cell, i.e., optoinjection, without significant cell damage because of a nonlinear interaction in a tiny focused spot. [6][7][8][9] Recently, the use of nanoparticles or microparticles has been accelerating attractive achievements to expand the capability of ultrashort laser optoinjection technology toward simultaneous treatment of multiple cells. Chakravarty et al 10 reported the delivery of DNA, protein, and fluorescence molecules into cells in a cuvette by using carbon black nanoparticles and a femtosecond laser.…”
mentioning
confidence: 99%
“…The perforation efficiency was studied in a separate experiment. Propidium iodide was added before laser manipulation at a concentration of 1.5 μ M as also described by Antkowiak et al and Mitchell et al [ 19 , 33 ]. Here, propidium iodide enters the cell due to membrane perforation.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a near infrared femtosecond (fs) laser has been employed for the nanoprocessing and photoinjection to plants 1618 . One of the main advantages of the fs laser photoinjection is the precise perforation capability at a subcellular resolution thanks to effective non-linear processes such as a multi-photon absorption at a laser focal point, which suppresses collateral damage in the optical path.…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell et al . 18 reported a systematic study of fs laser photoinjection efficiency of FITC-dextran into a tobacco BY-2 cell (TBY-2) considering the dependence on osmolarity, laser power and molecular weight of the conjugated dextran. They concluded that the introduction efficiency was significantly reduced with increasing molecular weight, and the maximum size of introduced dextran was 40 kDa under optimized conditions.…”
Section: Introductionmentioning
confidence: 99%